VEGETATIVE PROPAGATION OF COWPEA [VIGNA UNGUICULATA (L.) WALP] FOR INCREASED SEED PRODUCTION - Ibitoye, D.O.; Olomide, O.A.K. (Plant Breeding and Seed Science, 2016)
Large number of parental plants are required during hybridization in order to generate enough progeny needed for evaluation. Cowpea is propagated through seeds, this increases the waiting period as the plant has to complete its juvenile phase before flowering. Asexual propagation approach was employed on cowpea using the vine cuttings of flowering plants. The vine cuttings were planted in sterilized top soil and they began flowering 14 days after cutting without adding fertilizer. Success was obtained using this method which increases the rate at which the hybrids needed for multi-location trial were obtained.